THE SEMANTICS AND THE USES OF THE WORDS “BLIND” AND “KÖR” IN GERMAN AND IN TURKISH - Mehmet AYGÜN (Fırat University, 2019)
Some of the most significant components of lingual and cultural communication are words, idioms and proverbs. The words have connotations (symbolic, figurative) besides their real (basic) meanings. While a word has one real meaning, it may have several connotations. The first meaning that appears in mind is called real or basic meaning. The new meanings besides the real meanings of the words are called connotations (figurative). Besides the real meaning, connotations of words hold great significance while they are used. This fact is the field of “Semantics”. The utilization of words alone with their meaning they hold is examined in the field of “Word Semantics”. However, the utilization of words in some structures such as idioms, epigrams and proverbs is the subject of “Sentence Semantics” and they should be examined in that field. Although the words that are the holders of meaning and culture do not give much meaning alone, they have different meanings according to the user and the place where they are used. By gathering the words, some expression components such as idioms and proverbs are formed. They are generally used in more extensive and comprehensive meanings, different from the words that constitute them. As being richness of expression, the idioms and proverbs also reflect the life, culture and beliefs of the societies. While the idioms are formed as word groups, proverbs are the elements that hold the characterization of a sentence. In this study, the usage of the words in German and English that are subject to the research and the idioms and proverbs constituted by them will be examined.